Carbon Source Affects Synthesis, Structures, and Activities of Mycelial Polysaccharides from Medicinal Fungus Inonotus obliquus - He, Huihui; Li, Yingying; Fang, Mingyue; Li, Tiantian; Liang, Yunxiang; Mei, Yuxia (Journal of microbiology and biotechnology, 2021)
The effects of various carbon sources on mycelial growth and polysaccharide synthesis of the medicinal fungus in liquid fermentation were investigated. After 12-d fermentation, mycelial biomass, polysaccharide yield, and polysaccharide content were significantly higher in Glc+Lac group (glucose and lactose used as combined carbon source) than in other groups. Crude polysaccharides (CIOPs) and the derivative neutral polysaccharides (NIOPs) were obtained from mycelia fermented using Glc, fructose (Fru), Lac, or Glc+Lac as carbon source. Molecular weights of four NIOPs (termed as NIOPG, NIOPF, NIOPL, and NIOPGL) were respectively 780.90, 1105.00, 25.32, and 10.28 kDa. Monosaccharide composition analyses revealed that NIOPs were composed of Glc, Man, and Gal at different molar ratios. The NIOPs were classified as α-type heteropolysaccharides with 1→2, 1→3, 1→4, 1→6 linkages in differing proportions. In in vitro cell proliferation assays, viability of RAW264.7 macrophages was more strongly enhanced by NIOPL or NIOPGL than by NIOPG or NIOPF, and proliferation of HeLa or S180 tumor cells was more strongly inhibited by NIOPG or NIOPGL than by NIOPF or NIOPL, indicating that immune-enhancing and anti-tumor activities of NIOPs were substantially affected by carbon source. qRT-PCR analysis revealed that expression levels of phosphoglucose isomerase (PGI) and UDP-Glc 4-epimerase (UGE), two key genes involved in polysaccharide synthesis, varied depending on carbon source. Our findings, taken together, clearly demonstrate that carbon source plays an essential role in determining structure and activities of polysaccharides by regulating expression of key genes in polysaccharide biosynthetic pathway.